Analysis of neutron physics and thermal hydraulics for fuel assembly of small modular reactor loaded with ATFs. (March 2021) - Yu, Honghao; Cai, Jiejin; He, Sihong; Li, Xuezhong
Highlights: Neutron physics and thermal hydraulics calculations for small modular reactor loaded with ATFs. kinf of NuScale SMR is calculated, and it is found to be larger than the traditional reactor. NuScale has excellent performance, which can ensure the integrity of fuel under REA. Most ATFs can reduce the radial power peak, except U3 Si2 -SiC at BOC, and U3 Si2 -Zr, U3 Si2 -SiC, U3 Si5 -SiC at EOC. MFCT is significantly reduced by U3 Si2 -FeCrAl fuel rod under rod ejection accident. Abstract: The new small modular reactor (SMR) NuScale has been in the approval process for Nuclear Regulatory Commission by its off-site fabrication and assembly and good safety performance. To ensure the safety of the fuel rod the rod ejection accident at the beginning of cycle (BOC) and the end of cycle (EOC), the traditional fuel rod is replaced by accident tolerant fuels (ATFs). Neutron physics and thermal hydraulic analysis need to be performed before the actual application to ensure feasibility. In this paper, neutron physics and thermal hydraulics for SMR loaded with ATFs are analyzed. The results show that the 4% uranium enriched ATF pellets can meet the lifetime requirements, and the application of silicon uranium fuel pellets can significantly reduce maximum fuel centerline temperature (MFCT). Safety margin analysis was also performed for different ATF material failure criteria. The results show that ATF materials can enhance the safety of NuScale reactors.